A transformação humana pré-colombiana da paisagem florestal no interflúvio Purus-Madeira, Amazônia Central - Levis, Carolina (Instituto Nacional de Pesquisas da Amazônia - INPA, 2012)
Starting at least 3000 years before present, Native Amazonian populations expanded to several millions and developed efficient systems for managing forest resources, often creating oligarchic forests dominated by useful trees. The densest human populations were located along the major whitewater rivers. However, the scale and spatial distribution of forest modification is still unknown. Recent studies propose that human impact away from the rivers was minimal, which suggests that interfluves were relatively undisturbed in the past. Our study assessed the variations in the degree of past human manipulation of floristic composition in forests at six sites along the Purus-Madeira interfluve as a function of the distance from the main and secondary rivers. In all sites we inventoried useful trees with DBH ≥ 10 cm in two 1 ha plots and in five plots soil for charcoal analysis was collected in three soil pits. We also mapped archaeological evidence around the study sites. The shortest distance in kilometers from each plot to the rivers was calculated. To quantify forest manipulation, we measured the relative richness, abundance and basal area of useful trees, especially fruit trees and palms. We tested the relationships between these parameters and the plot s distance to the rivers and the difference of soil charcoal mass between the six sites. We found strong negative exponential relationships between forest manipulation and the distance to main and secondary rivers. Plots located from 10 km to 20 km from a main river had 20-40% useful tree species, plots with distances between 20-40 km had 15-25% useful trees, while plots greater than 40 km had less than 15%. Soil charcoal abundance was high in two sites with the shortest distances to secondary rivers. The shortest distance between plots and archaeological evidences was found in sites near rivers. These results strongly suggest that past forest manipulation by humans was not limited to the pre-Columbian settlements at the edges of the main rivers, but extended over interfluvial areas considered to be primary forest today. The sustainable use and conservation of Amazonian forest resources will be most effective if it considers the degree of past landscape domestication, as these landscapes concentrate useful plants related to human management.
Keywords: Ameríndios; Manejo da paisagem; Carvão